Analyzing the Labor Market Outcomes of Occupational Licensing. Issue 1 (17th December 2017) - Gittleman, Maury; Klee, Mark A.; Kleiner, Morris M.
Abstract : Recent assessments of occupational licensing have shown varying effects of the institution on labor‐market outcomes. This study revisits the relationship between occupational licensing and labor‐market outcomes by analyzing a new topical module to the Survey of Income and Program Participation. Relative to previously available data, the topical module offers more detailed information on occupational licensing attainment, with larger sample sizes and access to richer sets of person‐level characteristics. We find that those with a license earn higher pay, are more likely to be employed, and have a higher probability of employer‐sponsored health insurance offers.